International evidence on the link between foreign direct investment and economic freedom - Wan Ngah, Wan Azman Saini; Tun, Yin Li; Ibrahim, Saifuzzaman (Universiti Putra Malaysia Press, 2013)
Foreign direct investment (FDI) by multinational enterprises (MNEs) is considered as one of the key ingredients that drives the development process in many countries . However, the distribution of FDI across countries has not been uniform as only few countries have the ability to attract the bulk of FDI. In an effort to further understand the evolution in MNEs’ locational decision and their changing need, this paper examines whether economic freedom plays an important role in attracting FDI inflows. Hypothesis was tested based on the data gathered from 75 countries over the period 1981 to 2005 — using a system generalised method of moment (GMM) panel estimator. The result of this study shows the importance of economic freedom in attracting FDI inflows is undisputable. Furthermore an improvement in the freedom of economic provides a more enabling business environment.